Immunopathogenesis of Pneumocystis Pneumonia (PCP) and Its Clinical Implications - Malik, Andi Sri Suryani; Agustin, Heidy; Nurwidya, Fariz; Rozaliyani, Anna (Respiratory Science, 2025)
Pneumocystis pneumonia (PCP) is a serious lung infection caused by Pneumocystis jirovecii, primarily affecting immunocompromised individuals. It remains a major health concern, especially in HIV/AIDS patients and those undergoing immunosuppressive therapy. This review discusses how the immune system responds to P. jirovecii and why immunocompromised individuals are more vulnerable. In healthy individuals, CD4+ T cells, B cells, and macrophages help control the infection. However, in immunocompromised individuals, a weakened immune response allows fungal overgrowth, leading to severe lung damage. The review also covers symptoms, diagnosis, and treatment options. TMP-SMX is the preferred treatment, while alternative drugs are available for those who cannot tolerate it. Understanding the immune response to PCP can help improve treatment and patient care.